Evaluasi Komparatif Asam Sitrat Pada Beberapa Kultivar Mangga Lokal (Mangifera indica L.) dengan Metode Titrasi Alkalimetri - Choiril Hana Mustofa; Elsa Epilia Duri; Avanilla Fany Septyasari; Aristhasari Putri (Universitas Muhammadiyah Klaten, 2026)
Citric acid is an organic secondary metabolite found in fruit and is important in determining the sensory profile and biochemical stability of mango (Mangifera indica L.). This observational study aimed to quantitatively measure the prevalence of citric acid in three local mango varieties: Harumanis, Indramayu, and Manalagi. The methodology employed included qualitative identification through a precipitation reaction with calcium chloride (CaCl₂) and quantitative determination using an alkalimetric method. Qualitative test results on all three samples confirmed the presence of citric acid in all samples through the formation of calcium citrate precipitates. Quantitative analysis showed that the average citric acid content in Harumanis mangoes was 0.69%, Indramayu mangoes 0.98%, and Manalagi mangoes 0.92%. These findings indicate that the Indramayu variety has the highest citric acid content, which implies a potential longer shelf life compared to other varieties.